SOME FEATURES OF PHRASAL UNITS IN ENGLISH LANGUAGE - Rakhmonova Amira; Norbekova Maftuna (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Abstract. This article investigates the intriguing world of phrasal units, exploring their role as fundamental components of language and culture. Phrasal units, also known as fixed or multi-word expressions, are linguistic constructions that convey meanings beyond the literal interpretations of their constituent words. The article examines the stability and idiomatic nature of phrasal units, highlighting their resilience to linguistic change and their ability to serve as windows into the cultural and societal nuances of language. Through clear examples, the article demonstrates how phrasal units enrich communication by providing concise and nuanced expressions for complex concepts. Overall, the article underscores the significance of phrasal units as invaluable assets that contribute to the richness and depth of human communication.